The butter battle book - Seuss, Dr. (New York : Random House, 1984)
Engaged in a long-running battle, the Yooks and the Zooks develop more and more sophisticated weaponry as they attempt to outdo each other.
Book Links (A.L.A.).
Elem. School Library Collection.
School Library Journal.
Book Links (A.L.A.), March 2004.
Bulletin (Center for Children's books), May 2009.
Elem. School Library Collection, June 2000.
Keywords: Stories in rhyme; War -- Fiction; Stories in rhyme; War stories